2009
DOI: 10.1038/nmat2379
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral fullerenes for organic photovoltaic devices

Abstract: So far, one of the fundamental limitations of organic photovoltaic (OPV) device power conversion efficiencies (PCEs) has been the low voltage output caused by a molecular orbital mismatch between the donor polymer and acceptor molecules. Here, we present a means of addressing the low voltage output by introducing novel trimetallic nitride endohedral fullerenes (TNEFs) as acceptor materials for use in photovoltaic devices. TNEFs were discovered in 1999 by Stevenson et al. ; for the first time derivatives of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
548
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(574 citation statements)
references
References 21 publications
15
548
0
6
Order By: Relevance
“…Drees et al have recently demonstrated that lutetium based endohedral fullerenes (Lu 3 N@C 80 ) can be chemically derivatised with solubilising sidechains, and the resulting derivatives have LUMO energies up to 0.2-0.3 eV higher than PCBM. 25 Such derivatives exist as single isomers, preserving the beneficial self-organising and transport properties of PCBM, but increasing the available photovoltage to the cell.…”
Section: Factors Influencing the Structure And Performance Of Fullerementioning
confidence: 99%
“…Drees et al have recently demonstrated that lutetium based endohedral fullerenes (Lu 3 N@C 80 ) can be chemically derivatised with solubilising sidechains, and the resulting derivatives have LUMO energies up to 0.2-0.3 eV higher than PCBM. 25 Such derivatives exist as single isomers, preserving the beneficial self-organising and transport properties of PCBM, but increasing the available photovoltage to the cell.…”
Section: Factors Influencing the Structure And Performance Of Fullerementioning
confidence: 99%
“…The inefficacy of tuning frontier energy levels of fullerenes constrains donor material development 19, 20, 21, 22. Currently, the donor material design must reference the lowest unoccupied molecular orbital (LUMO) level of fullerene derivatives (e.g., [6,6]‐phenyl C 71 ‐butyric acid methyl ester, PC 70 BM) to optimize open‐circuit voltage ( V oc ) 23.…”
mentioning
confidence: 99%
“…Recently, a top-down graphene-to-fullerene conversion is even shown to be possible under particular conditions 13 . To exploit the unique mechanical and electrical properties of nanostructured carbon materials such as fullerenes, nanotubes and graphene for use in envisioned paradigm-shifting applications [14][15][16][17][18][19] , precise control over their formation must be achieved. Such control will only be forthcoming with the revelation of the primary chemical processes that govern their formation.…”
mentioning
confidence: 99%